The informativeness of field tests and laboratory assessments in forecasting the actual performance of swimmers - Zuoziene, I. J.; Pderys, J. (First international symposium sciences and practices in swimming, 2006)
The aim of this study was to compare the informativeness of field tests and laboratory assessments in forecasting the actual performance of athletes in the 50 m distance. The sample was comprised of 12 Lithuanian national category level swimmers (age - 18.63 ± 0.6 years, body mass - 72.6 ± 2.57 kg). The data obtained in the process of the research have shown that field tests, i.e. the results of measuring and tests done in the swimming-pool, are more suitable than the data of laboratory research for forecasting the results of swimmers in the 50m freestyle swim. The tests of the vertical high jump used for the assessment of the explosive force of athletes do not allow one to forecast the possibilities of the swimmer to achieve high results in the 50m swim. The components of speed and strength, however, as well as the index of fatigue correlate with the results achieved at the competition. These indices are significant and should be used in doing laboratory research in the functional condition and level of preparedness of swimmers.